Residents manage dynamic plant communities: Change over time in urban vegetation - Wheeler, Megan M.; Larson, Kelli L.; Cook, Elizabeth M.; Hall, Sharon J. (Frontiers in Ecology and Evolution, 2022)
Integrated social and ecological processes shape urban plant communities, but the temporal dynamics and potential for change in these managed communities have rarely been explored. In residential yards, which cover about 40% of urban land area, individuals make decisions that control vegetation outcomes. These decisions may lead to relatively static plant composition and structure, as residents seek to expend little effort to maintain stable landscapes. Alternatively, residents may actively modify plant communities to meet their preferences or address perceived problems, or they may passively allow them to change. In this research, we ask, how and to what extent does residential yard vegetation change over time? We conducted co-located ecological surveys of yards (in 2008, 2018, and 2019) and social surveys of residents (in 2018) in four diverse neighborhoods of Phoenix, Arizona. 94% of residents had made some changes to their front or back yards since moving in. On average, about 60% of woody vegetation per yard changed between 2008 and 2018, though the number of species present did not differ significantly. In comparison, about 30% of woody vegetation changed in native Sonoran Desert reference areas over ten years. In yards, about 15% of woody vegetation changed on average in a single year, with up to 90% change in some yards. Greater turnover was observed for homes that were sold, indicating a "pulse" of management. These results indicate that residential plant communities are dynamic over time. We observed greater vegetation turnover in the two older, lawn-dominated neighborhoods surveyed despite differences in neighborhood socioeconomic factors. This suggests that neighborhood age and other characteristics may be important drivers of change, while socioeconomic status neither promotes nor inhibits change at the neighborhood scale. Our findings highlight an opportunity for management interventions, wherein residents may be open to making conservation-friendly changes if they are already altering the composition of their yards.